The runaway - Petrie, Nicholas (A Peter Ash novel, 2022)
"When Peter Ash rescues a stranded woman, he finds she's in far deeper trouble than he could ever imagine. Working nights at a gas station in an isolated Montana town, Helene is desperate to escape both her low-paying job and her predatory boss. So when a kind stranger stops to fill up his tank, Helene barely hesitates before asking for a ride, willing to go anywhere to start her life over. But she may have fled one danger only to run straight into another. War veteran Peter Ash is driving through northern Nebraska when he encounters a young pregnant woman alone on a gravel road, her car dead. Never one to abandon someone in distress, Peter offers her a lift, but what begins as an act of kindness soon turns into a deadly cat-and-mouse chase across the lonely highways with the woman's vicious ex-cop husband hot on their trail. The pregnant woman has seen something she was never meant to see... but protecting her might prove to be more than Peter can handle. In order to save the woman and himself, Peter must use everything he has learned during his time as a Marine, including his knowledge of human nature, in order to escape a ruthless killer with instincts and skills that match - and perhaps exceed - Peter's own.